Eficácia e dinamismo da política fiscal: uma discussão entre a visão de Keynes e da Equivalência Ricardiana - Cardoso, André Bologna de Castro (2018)
Fiscal policy has always been a source of controversy among the various currents of economic thought. After the Great Depression of 1929, fiscal policy, influenced by the thinking of John Maynard Keynes, gained preponderance status in sustaining aggregate demand. However, from the 1970s onwards, it was considered ineffective to influence the economy and was subordinated to monetary policy. The crisis of 2008 brought important revisions in the conventional view on the role of politics. Before being reduced to mere secondary instrument of economic policy, in the current economic debate, especially with the limitations in the monetary policy, fiscal actions were elevated to greater protagonism. The objective of this paper is to discuss the effectiveness and dynamism of fiscal policy under two different prisms: Keynes vision and Ricardian Equivalence. From this reading of Keynes on fiscal policy we try to make the Ricardian Equivalence critique trying to demonstrate that fiscal policy is an important economic policy, because it has dynamisms and its effects are important for the economy as a whole